Histological and immunocytochemical study of cervical intraepithelial neoplasia (CIN) with associated HPV 6 and HPV 16 infections. Issue 11 (November 1986) - Jenkins, D; Tay, S K; McCance, D J; Campion, M J; Clarkson, P K; Singer, A
Abstract : Histological and immunocytochemical features of cervical intraepithelial neoplasia (CIN) associated with HPV 6 and HPV 16, either singly or in combination, were studied in 48 cases. Features of HPV infection (koilocytosis, binucleation, multinucleation, giant irregular nuclei and individual cell dyskeratosis) were present in high prevalence in both HPV 6 and HPV 16 associated CIN. Abnormal mitoses seemed to be a good indicator of CIN and were present in about 50% of cases of CIN associated with either HPV 6 or HPV 16 infection. This finding provides no support for the view held by some investigators that associated HPV 16 infection can be predicted by the presence of abnormal mitoses. Expression of HPV antigen was shown in about 40% of cases with a slight, but not significantly, higher prevalence in cases of combined HPV 6 and HPV 16 infection. Conventional histology and immunocytochemistry could not distinguish CIN associated with HPV 6 from CIN associated with HPV 16 infection.